2010
DOI: 10.2172/979448
|View full text |Cite
|
Sign up to set email alerts
|

Novel Adsorbent-Reactants for Treatment of Ash and Scrubber Pond Effluents

Abstract: The overall goal of this project was to evaluate the ability of novel adsorbent/reactants to remove specific toxic target chemicals from ash and scrubber pond effluents while producing stable residuals for ultimate disposal. The target chemicals studied were arsenic (As(III) and As(V)), mercury (Hg(II)) and selenium (Se(IV) and Se(VI)). The adsorbent/reactants that were evaluated are iron sulfide (FeS) and pyrite (FeS 2 ). Procedures for measuring concentrations of target compounds and characterizing the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…In short, 0.1 M Na 2 S and 0.1 M FeCl 2 were initially mixed with equivalent volume ratio and then they were aged for 3 days. According to previous result, the synthesized FeS was identified to amorphous mackinawite [19]. The surface area of synthesized FeS was reported in literatures, ranging from 0.05 to 424 m 2 /g [22,23].…”
Section: Methodsmentioning
confidence: 63%
See 1 more Smart Citation
“…In short, 0.1 M Na 2 S and 0.1 M FeCl 2 were initially mixed with equivalent volume ratio and then they were aged for 3 days. According to previous result, the synthesized FeS was identified to amorphous mackinawite [19]. The surface area of synthesized FeS was reported in literatures, ranging from 0.05 to 424 m 2 /g [22,23].…”
Section: Methodsmentioning
confidence: 63%
“…Previous research has demonstrated that mackinawite (FeS) can be a good reactant/adsorbent to remove selenium from water [19]. This study aims to provide fundamental information on the behavior of Se with adsorbent/reactant (FeS) as well as the basis for development of treating processes for ash and scrubber pond waters at coal-fired power plants that will be effective in removing Se and will produce residuals with low solubility.…”
Section: Introductionmentioning
confidence: 99%